The Social Marginalization of People Living with a Mentally Ill Label–Family, Friends, and Work - Maloušková, Kateřina; Fafejta, Martin (Qualitative Sociology Review, 2021)
This paper is based on qualitative research among people diagnosed with a mental illness who voluntarily attend a mental health center. Such individuals are given a degrading “mentally ill” label, which transforms them into a “new” person. This study showed that—due to their label—research participants are often socially marginalized—not only in the public but also in the private sphere. As members of an “organized deviant group” (the mental health center), they follow a “deviant career” and find a job outside the regular job market. Their marginalization is not only caused by their health problems (by their impairment), but they are also disabled through social reactions to these problems. Psychiatry based on the biological model of the disease cannot, therefore, help them without the cooperation of social science approaches dealing with social marginalization.